Prinsip Miranda Rule Sebagai Hak Asasi Tersangka Dalam Sistem Peradilan Pidana Indonesia - Muammar, Muammar; Baharuddin, Wahdaniah (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2022)
Introduction: Often in the law enforcement process there is a form of crime, neglect of obligations, human rights violations related to the civil rights of citizens in the criminal justice system and abuse of power committed by apparat. In our criminal justice system, the rights of suspects who are the basis of human rights attached to them are often overlooked, which is detrimental to suspects. Purposes of the Research: This research aims to find out how the Miranda Rule principle guarantees the human rights of suspects in the Indonesian criminal justice system. Methods of the Research: The methods used in this research are normative research methods, using a conceptual approach and a statute approach. Results Originality of the Research: the results showed that the Miranda Rule/Miranda Principle, in the form of Miranda Rights has provided guarantees for the rights of suspects. Namely, the right to obtain/contact legal counsel/advocate, and if unable to, then the right to be provided with legal counsel/advocates, the right to obtain legal assistance has been absorbed into articles 54, 55, and 114 of the Criminal Procedure Code of Indonesia, while if he is incapacitated, then the suspect has the right to be provided with legal counsel by the official concerned or through an investigator, as stipulated in article 56 paragraph 1 of the Criminal Procedure Code of Indonesia. As for the Miranda Warning (Right To Remain Silent), it is not expressly regulated, but implicitly it can be interpreted as its application in articles 52, 117 and 166 of the Criminal Procedure Code of Indonesia.